2022
DOI: 10.1371/journal.pntd.0010982
|View full text |Cite
|
Sign up to set email alerts
|

Case-control investigation of invasive Salmonella disease in Malawi reveals no evidence of environmental or animal transmission of invasive strains, and supports human to human transmission

Abstract: Background Invasive Salmonella infections cause significant morbidity and mortality in Sub-Saharan Africa. However, the routes of transmission are uncertain. We conducted a case-control study of index-case and geographically-matched control households in Blantyre, Malawi, sampling Salmonella isolates from index cases, healthy people, animals, and the household environment. Methodology Sixty index cases of human invasive Salmonella infection were recruited (March 2015-Oct 2016). Twenty-eight invasive Non-Typh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 48 publications
2
10
0
Order By: Relevance
“…Previous index patient-household studies from Burkina Faso (rural areas) and Malawi (urban slums) also found matching index patient-household member pairs of S . Typhimurium ST313 and ST3257 (an ST type closely related to ST313), whereas animal and environmental sources did not reveal ST313 (Post et al, 2019 ; Koolman et al, 2022 ). For S .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous index patient-household studies from Burkina Faso (rural areas) and Malawi (urban slums) also found matching index patient-household member pairs of S . Typhimurium ST313 and ST3257 (an ST type closely related to ST313), whereas animal and environmental sources did not reveal ST313 (Post et al, 2019 ; Koolman et al, 2022 ). For S .…”
Section: Discussionmentioning
confidence: 99%
“…However, this hypothesis should be further explored in longitudinal studies assessing carriage duration (Phoba et al, 2020 ). Furthermore, the incremental evidence of a human reservoir of the iNTS (Kariuki et al, 2019 , 2020 ; Post et al, 2019 ; Kasumba et al, 2021 ; Koolman et al, 2022 ) and the absence of evidence for a major environmental reservoir (Crump et al, 2015 , 2021 ) do not preclude co-existent environmental reservoirs and transmission routes of the iNTS (Kariuki et al, 2019 ; Mbae et al, 2020 ; Tack et al, 2021 ; Falay et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Three pairs of index patients and their households were identified by Multilocus variable‐number tandem‐repeat analysis (MLVA) (identical or similar MLVA type) and WGS analyses (household isolates have 0–2 SNPs from the index isolates), but we did not find matched pairs from livestock and water samples. Similarly, in Malawi, Koolman et al 20 observed two pairs of index cases and their asymptomatic household members from 60 index cases, but they did not detect overlaps between iNTS isolates and animal or environmental isolates. In this study, four invasive S .…”
Section: Figurementioning
confidence: 96%
“…It is not certain how these pathogens are transmitted, but there is increasing evidence from case-control studies that ST313 strains are human-associated but not animal-associated within households (Post et al 2019 , Koolman et al 2022 ). A recent summary concludes that the available data are consistent with iNTS disease being transmitted person-to-person (Chirwa et al 2023 ).…”
Section: Introductionmentioning
confidence: 99%